PENERAPAN STANDAR PELAYANAN PUBLIK TERHADAP PENYANDANG DISABILITAS PADA YAYASAN SAYAP IBU KOTA TANGERANG SELATAN - Fildzah Amalia, Sharfina; Khoirul Anwar, Muhammad (Journal of Research and Publication Innovation, 2024)
The research shows that the Disability Service Unit Foundation applies transparency, accountability, and conditional functions in its services. There is also community participation in program implementation, services without discrimination, and a balance of rights and obligations between service providers and recipients. Researchers aim to analyze and describe the public service standards carried out by the mother wing foundation. Researchers conducted with a qualitative approach method and data collection techniques of observation, interviews, and documentation. The theory put forward by Lijan Poltak in Sinambela (2006) includes public service standards which have 6 indicators in them, namely transparency, accountability, conditionality, participation, equal rights, and balance of rights and obligations, to analyze and observe the Mother's Wing Foundation in South Tangerang. The results of the research at the Mother's Wing Foundation show that each indicator has been running well, but there are some shortcomings in the services at the Mother's Wing Foundation.